Analisis Regresi Linear Berganda Untuk Melihat Faktor Yang Berpengaruh Terhadap Kemiskinan di Provinsi Sumatera Barat - Rahmadani Agung Prasetyo; Helma Helma (UNIVERSITAS NEGERI PADANG, 2022)
Poverty was one of the sources of problems that indirectly affect development, followed by the problem of unemployment and interrelated inequalities. Changes in the poor population are quite volatile at West Sumatra. This caused by many factors. This study goals to find out the factors that cause significant fluctuations in poverty at West Sumatra. The research was conducted using the concept of applied research which was opened with a literature study followed by data collection. The results of the study in the form of a model of certain things / events that have a significant influence on the poverty level of the research area obtained through multiple linear regression analysis are :y ̂=203399+0,05178x_1-1040x_4+815x_6Thus, the factors that significantly affect the poverty level of the study area are population (x_1), human development index (x_4) and life expectancy (x_6) with an error rate of 5%.ABSTRAK (10 PT)